2021
DOI: 10.1016/j.atherosclerosis.2021.05.007
|View full text |Cite|
|
Sign up to set email alerts
|

APOE gene variants in primary dyslipidemia

Abstract: Apolipoprotein E (apoE) is a major apolipoprotein involved in lipoprotein metabolism. It is a polymorphic protein and different isoforms are associated with variations in lipid and lipoprotein levels and thus cardiovascular risk. The isoform apoE4 is associated with an increase in LDL-cholesterol levels and thus a higher cardiovascular risk compared to apoE3. Whereas, apoE2 is associated with a mild decrease in LDL-cholesterol levels. In the presence of other risk factors, apoE2 homozygotes could develop type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 78 publications
(66 citation statements)
references
References 114 publications
1
52
0
Order By: Relevance
“…These isoforms differ considerably in terms of their receptor-binding or functional activities. Indeed, ApoE2 (cys112, cys158) has been reported to be defective for receptor binding and has been implicated in several diseases, including type III hyperlipoproteinemia [ 11 ]. ApoE4 (arg112, arg158) has low molecular stability, which influences its ability to bind lipoproteins, and has been implicated in the development of atherosclerosis and neurological disorders.…”
Section: Apolipoprotein Ementioning
confidence: 99%
“…These isoforms differ considerably in terms of their receptor-binding or functional activities. Indeed, ApoE2 (cys112, cys158) has been reported to be defective for receptor binding and has been implicated in several diseases, including type III hyperlipoproteinemia [ 11 ]. ApoE4 (arg112, arg158) has low molecular stability, which influences its ability to bind lipoproteins, and has been implicated in the development of atherosclerosis and neurological disorders.…”
Section: Apolipoprotein Ementioning
confidence: 99%
“…To the best of our knowledge, no mutation in the PCSK9 gene in the Czech population has been reported to date. An important role is also played by the apolipoprotein E ( APOE ) gene, which affects the levels of LDL-C thus contributing to higher LDL-C levels in FH patients ( Pirillo et al, 2017 ; Rashidi et al, 2017 ; Khalil et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a review study reported that the common and rare APOE variants alongside environmental factors and epigenetics are associated with variations in lipids and lipoprotein levels affecting the clinical presentation of dyslipidemia (39). Together, these results indicated that molecular screening of the APOE gene and study of epigenetic variations are crucial to understanding the implications of the APOE variants in each of these diseases, which would be possible using high throughput sequencing, i.e NGS.…”
Section: Discussionmentioning
confidence: 99%